2009
DOI: 10.1007/s11332-009-0083-9
|View full text |Cite
|
Sign up to set email alerts
|

Injury incidence rate, severity and diagnosis in male volleyball players

Abstract: The aim of this study was to record the injury incidence in all age categories in male volleyball players and clarify the role of age in injury occurrence. The injury incidence rate, severity, diagnosis and the anatomical location of the injuries that occurred during practice and competition in the whole championship period were recorded prospectively during the period 2005-2006. A total of 407 Greek male volleyball players participating in all Volleyball Championships in Greece according to the Greek Volleyba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 26 publications
2
28
2
6
Order By: Relevance
“…They reported 248 injuries over a total exposure time of 110.596 h, representing an overall incidence of 0.60 injuries per player. Zetou et al (2006) and Beneka et al (2009) found higher results than those found in our study. In addition to these studies, Aagaard and Jorgensen (1996) previously reported a rate of injuries corresponding to 1.5 injuries per player for Danish male volleyball players.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…They reported 248 injuries over a total exposure time of 110.596 h, representing an overall incidence of 0.60 injuries per player. Zetou et al (2006) and Beneka et al (2009) found higher results than those found in our study. In addition to these studies, Aagaard and Jorgensen (1996) previously reported a rate of injuries corresponding to 1.5 injuries per player for Danish male volleyball players.…”
Section: Discussioncontrasting
confidence: 91%
“…As opposed to our study, Kugler et al (2006) reported 1294 injuries among 625 indoor volleyball players, representing an overall incidence of 0.22 injuries per player per year. It might be considered that differences of results between our study and other studies such as Zetou et al (2006), Kugler et al (2006), and Beneka et al (2009) are due to differences of league levels and using different research methods employed in the studies. There are many studies related to sports injuries which focus on the relationship between sports injuries and performance levels.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Reeser et al [13] reported that 57% of male volleyball athletes (21.5 years average age) informed them of a history of shoulder problems during the preceding competitive season. However, Beneka et al [14] recorded the injury rate of all age categories of Greek male volleyball and confirmed that the prevalence of injuries for 15-18-year-old volleyball players was significantly lower than that for older players. According to Reeser et al [10], age, position played, and serving style are three possible factors associated with shoulder problems.…”
Section: Discussionmentioning
confidence: 99%